KEPUASAN KERJA PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBERDAYA MANUSIA (BKPSDM) BALIKPAPAN - Tamzil Yusuf; Misna Ariani; Tutik Yuliani; Yudhi Hendrawan; Ilham Wahyudi (Jurnal GeoEkonomi, 2024)
The efforts of the Personnel and Human Resources Development Agency (BKPSDM) in Balikpapan to find out employee job satisfaction in order to support the achievement of the vision and mission of (BKPSDM) in Balikpapan. Job satisfaction in this study, seen from the influence of work stress, motivation and work environment. Respondents in this study were 44 employees of BKPSDM, using quantitative research methods. Data collection was done by means of a questionnaire, then the results of the questionnaire were carried out by instrument testing, classical assumption testing, multiple linear analysis techniques and partial hypothesis testing (t-test). The results showed that the variable of work stress had a positive and insignificant effect on job satisfaction, while the variables of motivation and work environment had a positive and significant effect on job satisfaction at the Staffing and Human Resource Development Agency (BKPSDM) in Balikpapan.